Facilitatory Mechanisms Shape Selectivity for the Rate and Direction of FM Sweeps in the Inferior Colliculus of the Pallid Bat - Williams, Anthony J. (American Physiological Society, 2010)
The inferior colliculus (IC) of the pallid bat has a large percentage of neurons that respond selectively to the rate and direction of the bat's echolocation pulse, a downward FM sweep. Three underlying mechanisms have been previously described. Here we describe a fourth mechanism, facilitation, that shapes selectivity for both sweep rate and direction. The neurons studied are termed FM specialists, because they do not respond to tones. Most were selective for the downward sweep direction, and this preference was expressed even when presented with narrowband, 1 kHz sweeps that crossed only a fraction of their excitatory receptive fields. This selectivity was also expressed in response to two tones delayed in time, termed two-tone facilitation (TTF). Direction-selective neurons showed a greatly facilitated response when a higher-frequency tone preceded a lower-frequency tone, simulating conditions in a downward sweep. The degree of temporal asymmetry in facilitation accurately predicted direction selectivity. When the spectral difference between the two tones was increased, the best delay also increased and could be used to predict a neuron's preferred sweep rate. To determine whether TTF alone created rate and direction selectivity, low- and high-frequency inhibitory sidebands, which can also shape selectivity, were eliminated from sweeps. In most cases, selectivity persisted. These results support the idea of spectral delay lines that produce an overlap and summation of excitatory inputs only when a dynamic stimulus traverses a receptive field in one direction at a specific velocity.